2011
DOI: 10.1128/jb.01096-10
|View full text |Cite
|
Sign up to set email alerts
|

EsaD, a Secretion Factor for the Ess Pathway inStaphylococcus aureus

Abstract: Staphylococcus aureus encodes the Sec-independent Ess secretion pathway, an ortholog of mycobacterial T7 secretion systems which is required for the virulence of this Gram-positive microbe. The Ess (ESX secretion) pathway was previously defined as a genomic cluster of eight genes, esxA, esaA, essA, essB, esaB, essC, esaC, and esxB. essABC encode membrane proteins involved in the stable expression of esxA, esxB, and esaC, genes specifying three secreted polypeptide substrates. esaB, which encodes a small cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 34 publications
(45 reference statements)
2
88
0
Order By: Relevance
“…The average load of S. aureus USA300 per gram of kidney tissues was 7.9 log 10 CFU, and it was 7.4 log 10 CFU for the isogenic ΔessE mutant (Fig. 6B) (P ϭ 0.0024), a reduction similar to that observed for other mutant alleles of the ESS cluster (15,18). Immunohistochemical analysis of thin-sectioned tissue was used to assess the abundance of anti-F4/80-positive macrophages and of RANTES production in renal abscess lesions.…”
Section: Mouse Cytokine Responses During Bloodstream Infection With Wmentioning
confidence: 55%
See 1 more Smart Citation
“…The average load of S. aureus USA300 per gram of kidney tissues was 7.9 log 10 CFU, and it was 7.4 log 10 CFU for the isogenic ΔessE mutant (Fig. 6B) (P ϭ 0.0024), a reduction similar to that observed for other mutant alleles of the ESS cluster (15,18). Immunohistochemical analysis of thin-sectioned tissue was used to assess the abundance of anti-F4/80-positive macrophages and of RANTES production in renal abscess lesions.…”
Section: Mouse Cytokine Responses During Bloodstream Infection With Wmentioning
confidence: 55%
“…Earlier work reported that mutations in genes for substrates of ESS secretion (esxB, esxC, or esxD) resulted in defects of S. aureus essD expression (17,18). The Esx secretion defect for mutants with defects in other ess genes had also been attributed to the loss of essD expression (17).…”
mentioning
confidence: 99%
“…T7SS was initially described and termed the 'ESX protein secretion system' in pathogenic mycobacteria [23] belonging to the class Actinobacteria with high GC content. Subsequently, a related secretion system (ESS protein secretion) was detected in some Firmicutes bacteria, including Staphylococcus aureus [24][25][26][27][28][29], Listeria monocytogenes [21,30], Bacillus subtilis [21,30] and Streptococcus agalactiae [21,30]. We have identified an ESS secretion system in S. iniae, which also belongs to the low-GC Firmicutes bacterial group.…”
Section: Iusa1 and Sf1mentioning
confidence: 91%
“…Previous investigations have demonstrated a crucial role of T7SS in bacterial survival within the host [21,23,31,32], consistent with transmission electron micrographs of interactions between S. iniae DX09 and spleen cells from diseased catfish. Moreover, considerable evidence is available supporting essential roles of the actinobacterial ESS protein secretion system in virulence [26][27][28][29].…”
Section: Iusa1 and Sf1mentioning
confidence: 99%
See 1 more Smart Citation